2019
DOI: 10.1007/s11356-019-07379-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of mixtures of glyphosate with 2,4-dichlorophenoxyacetic acid chemical forms towards Cnesterodon decemmaculatus (Pisces, Poeciliidae)

Abstract: Acute genotoxicity of commercial glyphosate (GLY) (Credit®)-, 2,4-D-acid (2,4-D) (Dedalo Elite)-, 2,4-D-amine (2,4-D DMA) (Weedar Full®)-and 2,4-D-ester (2,4-D BE) (Herbifen Super®)-based herbicide formulations alone and their combinations were analysed in Cnesterodon decemmaculatus. Mortality was evaluated as a lethal end-point and the single cell gel electrophoresis (SCGE) bioassay was used as a sublethal end-point. LC50 96h values for Dedalo Elite was 0.46 mg/L and Herbifen Super® was 2.67 mg/L based on 2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…So, paraquat highly accumulated in renal cells since the export of paraquat from the apical membrane of tubular cells into the tubule lumina for excretion via MATE1 was decreased [ 64 ]. Likewise, the combination of glyphosate plus 2,4-D enhanced the genetic damage in Cnesterodon decemmaculatus model [ 65 ]. Our research also has limitations that the lack of non-exposure group as a reference level of biomarker in healthy subjects since non-exposure group in the same anthropometric characteristics for this study area would be difficult to recruit.…”
Section: Discussionmentioning
confidence: 99%
“…So, paraquat highly accumulated in renal cells since the export of paraquat from the apical membrane of tubular cells into the tubule lumina for excretion via MATE1 was decreased [ 64 ]. Likewise, the combination of glyphosate plus 2,4-D enhanced the genetic damage in Cnesterodon decemmaculatus model [ 65 ]. Our research also has limitations that the lack of non-exposure group as a reference level of biomarker in healthy subjects since non-exposure group in the same anthropometric characteristics for this study area would be difficult to recruit.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, surface-confined interaction of DNA 6 and 2,4-D was performed at the surface of disposable pencil graphite electrodes (PGEs), then, the oxidation signal of guanine was measured. The experimental parameters were optimized and the interaction was also evaluated in the presence of another herbicide, glyphosate which is widely used in combination with 2,4-D for weed control [46,47].…”
Section: Tablementioning
confidence: 99%
“…In the next step of the study, the interaction process was investigated in the presence of a different pesticide, GLY under optimum conditions (Figure 11). It is known that the mixture of 2,4-D and GLY has been widely used for weed control [46,47]. Thus, the effect of 2,4-D onto DNA was compared to the one occurred in the presence of GLY.…”
Section: Figure 10mentioning
confidence: 99%
“…Moreover, the acute toxicity of glyphosate-based pesticides, as Atanor®, Credit®, Glifloglex®, and Roundup Ultra Max®, was informed in the range of 19.4 mg/L and 78.18 mg/L (Brodeur et al 2014;Soloneski et al 2016). It has been previously demonstrated that glyphosate causes oxidative stress, inhibits the action of key enzymes for regulation of cell cycle, and produces genotoxic damage on amphibian larvae (Carvalho et al 2020;Lima et al 2020). Toxicity studies of 2,4-D on amphibians have shown that the herbicide inhibits oocyte maturation (LaChapelle et al 2007;Stebbins-Boaz et al 2004) and has teratogenic effects on Xenopus laevis (Morgan et al 1996) and Rhinella arenarum, one of the most susceptible amphibian species during the embryo-larval period (Aronzon et al 2011).…”
Section: Introductionmentioning
confidence: 99%